Community Plantation Forests: As Implementation of Agrarian Reform in Forestry Sector Village Lubuk Seberuk, Lempuing OKI, South Sumatera - Almira Gusti Iqma; Genta Mahardhika Rozalinna (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2020)
This study aims to analyze agrarian reform policies in the management of Community Plantation Forests (HTR) in Lubuk Seberuk Village. In terms of methodology, this study uses a literature review - a qualitative approach. The results showed that the Community Plantation Forest (HTR) in Lubuk Seberuk Village is an effort to deal with land conflicts and improve the economy of the surrounding community. The people in Lubuk Seberuk Village have already reaped the rewards from managing rubber plantations so that they are able to pay for children's education up to university level thanks to the HTR rubber plantation. In addition, there is a Community Plantation Forest Timber Forest Product Utilization Permit (IUPHHK-HTR), which is expected by individuals or cooperatives to be able to increase the potential and quality of production forests.Keywords: Agrarian Reform; Community Plantation Forests; Community Plantation Forest Timber Forest Product Utilization Permit (IUPHHK-HTR); Production Forests Penelitian ini bertujuan untuk menganalisis kebijakan reforma agraria pada pengelolaan kawasan Hutan Tanaman Rakyat (HTR) di Desa Lubuk Seberuk. Dari sisi metodologi, penelitian ini menggunakan kajian literatur – pendekatan kualitatif. Hasil penelitian menunjukkan bahwa Hutan Tanaman Rakyat (HTR) di Desa Lubuk Seberuk merupakan salah satu upaya untuk menangani konflik lahan dan meningkatkan perekonomian masyarakat sekitar. Masyarakat di Desa Lubuk Seberuk sudah memetik hasil dari mengelola kebun karet hingga sudah mampu membiayai pendidikan anak-anak hingga ke jenjang perguruan tinggi berkat hasil kebun karet HTR. Disamping itu, terdapat Izin Usaha Pemanfaatan Hasil Hutan Kayu Hutan Tanaman Rakyat (IUPHHK-HTR), yang diharapkan perorangan atau koperasi mampu untuk meningkatkan potensi dan kualitas hutan produksi.Kata kunci: Reforma agraria; Hutan Tanaman Rakyat (HTR); Izin Usaha Pemanfaatan Hasil Hutan Kayu Hutan Tanaman Rakyat (IUPHHK-HTR); Hutan Produksi